2020
DOI: 10.1210/clinem/dgaa798
|View full text |Cite
|
Sign up to set email alerts
|

Role of Age at Diagnosis in Defining Potential Familial Nonmedullary Thyroid Cancer in Kindreds With Two Affected Members

Abstract: Context The definition of familial non medullary thyroid cancer (FNMTC), as presence of the disease in two or more first degree relatives, is controversial due to the high probability to observe a sporadic association when only two members are affected. Objective To evaluate the role of age at diagnosis in differentiating the true cases of FNMTC. Design, Setting, Participants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…Moreover, in familial NMTC, the rate of SMN correlated with the number of affected members and the risk of SMN was primarily driven by families with more than two members. Following our recent paper (12), we evaluated the rate of SMN, in FNMTC kindreds with two affected members, considering the age at diagnosis. In familial NMTC kindreds in which age at diagnosis was equal to or less than 45 years in both affected members, the rate of SMN was significantly higher than observed in sporadic NMTC (20.3% vs. 5.3%, p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in familial NMTC, the rate of SMN correlated with the number of affected members and the risk of SMN was primarily driven by families with more than two members. Following our recent paper (12), we evaluated the rate of SMN, in FNMTC kindreds with two affected members, considering the age at diagnosis. In familial NMTC kindreds in which age at diagnosis was equal to or less than 45 years in both affected members, the rate of SMN was significantly higher than observed in sporadic NMTC (20.3% vs. 5.3%, p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors consider kindred with only two affected members a fortuitous association, whereas only families with 3 or more affected first-degree relatives should be considered FNMTC. Recently, our group suggested that the definition of FNMTC in kindred with only 2 affected members should also take into account the age at diagnosis as a key element of familial cancer (12). There are still many unclear aspects concerning definition, clinical behavior, and genetic mechanisms underlying this type of thyroid cancer (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…19 Although some authors define FNMTC only when three or more relatives are affected, many studies recommend the definition of ≥2 affected relatives used here. [7][8][9][10][11][13][14][15][16][17][18]20 It should be noted that one first-degree relative with thyroid cancer is sufficient to increase the individual's risk of disease. [1][2][3][4][5][6] Furthermore, a meta-analysis of 12 studies demonstrated a higher risk of recurrence and lower survival in patients with FNMTC (vs. patients with sporadic tumour).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Some studies have also shown that familial non-medullary thyroid carcinoma (FNMTC) is more aggressive on presentation and is associated with a higher risk of recurrence and even with lower survival than sporadic tumour. [7][8][9][10][11][12][13][14][15][16] This greater aggressiveness of FNMTC has also been suggested for the paediatric population. 15,16 Finally, in individuals submitted to ultrasonography (US) screening because of a family history of thyroid cancer, tumours are diagnosed at an earlier stage (smaller size and lower frequency of extrathyroidal invasion and lymph node metastases) compared to their relatives whose diagnosis was not made by screening.…”
Section: What This Paper Addsmentioning
confidence: 97%
“…Recentemente è stato suggerito di utilizzare, nelle famiglie con due soli affetti, l'età alla diagnosi come criterio differenziale. Secondo questo studio, se il probando e il familiare affetto hanno entrambi, al momento della diagnosi della malattia, un'età inferiore ai 45 anni, il rischio di un'associazione casuale potrebbe essere minimo dal momento che le forme familiari sono generalmente caratterizzate da una precoce età di insorgenza e dal fenomeno dell'anticipazione genica [5].…”
Section: Definizioneunclassified